2019
DOI: 10.1186/s13293-019-0257-3
|View full text |Cite
|
Sign up to set email alerts
|

Muscle metabolism and atrophy: let’s talk about sex

Abstract: Skeletal muscle health is a strong predictor of overall health and longevity. Pathologies affecting skeletal muscle such as cancer cachexia, intensive care unit treatment, muscular dystrophies, and others are associated with decreased quality of life and increased mortality. Recent research has begun to determine that these muscular pathologies appear to present and develop differently between males and females. However, to our knowledge, there has yet to be a comprehensive review on musculoskeletal difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
124
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 151 publications
(128 citation statements)
references
References 197 publications
(309 reference statements)
3
124
0
1
Order By: Relevance
“…Like other physiological systems (Hefferan et al, 2003;Glenmark et al, 2004;Foley et al, 2005), muscle displays sexbased differences in both phenotype and mechanism during states of enforced disuse (Ploutz-Snyder et al, 2014;Rosa-Caldwell and Greene, 2019). Since few studies have aimed at investigating male and female rats concomitantly, and because of the various models and durations employed, a consensus has yet to be reached regarding the effect of sex differences in muscle deconditioning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like other physiological systems (Hefferan et al, 2003;Glenmark et al, 2004;Foley et al, 2005), muscle displays sexbased differences in both phenotype and mechanism during states of enforced disuse (Ploutz-Snyder et al, 2014;Rosa-Caldwell and Greene, 2019). Since few studies have aimed at investigating male and female rats concomitantly, and because of the various models and durations employed, a consensus has yet to be reached regarding the effect of sex differences in muscle deconditioning.…”
Section: Discussionmentioning
confidence: 99%
“…In Wistar rats, it has been shown that males have myofibers with greater cross-sectional area than females (Deschenes et al, 2018), and that they display a greater proportion of type 1 myofibers (Simard et al, 1987;Nakano et al, 1995;Novák et al, 2010), especially in the soleus, one of the muscles that atrophies most rapidly in response to mechanical unloading. Since unloadinginduced atrophy primarily affects oxidative (type 1) myofibers (Rosa-Caldwell and Greene, 2019), and leads to a fiber switch from type 1 to type 2 (Mortreux et al, 2019b), it is likely that partial mechanical unloading will yield different results in females compared to male rats, and thus demand for specific mitigating strategies.…”
Section: Introductionmentioning
confidence: 99%
“…There are clear sex differences in skeletal muscle kinetics and fiber-type composition [41]. In addition, there are several theoretical explanations for sex differences in muscle wasting, including the anabolic effects of testosterone, and the anti-inflammatory effects of estrogen [42,43]. Testosterone deficiency is especially common in male dialysis patients with low muscle mass [44] and this may have contributed to the greater LTM loss over time.…”
Section: Discussionmentioning
confidence: 99%
“…However, the astronauts’ population remains very heterogeneous in sex, age, mission duration, and mission protocols. More so, it is clear males and females have different musculoskeletal [ 117 , 118 , 119 ], cardiovascular [ 120 , 121 ] and overall physiology that may contribute to differential responses to micro- and partial gravity. As such, it is of the utmost importance to study adult female animals, in order to understand the sex-based differences in the adaptations to partial gravity, and thus develop the best countermeasures for both males and females.…”
Section: Future Perspectivesmentioning
confidence: 99%